2022
DOI: 10.1097/icu.0000000000000912
|View full text |Cite
|
Sign up to set email alerts
|

Management of inflammation after the cataract surgery

Abstract: Purpose of reviewTo review most recent studies and clinical trials regarding pathogenesis, treatment, and prevention of inflammation after the cataract surgery.Recent findings FLACS gave opportunity to evaluate inflammatory cytokines in the aqueous humour right after the laser procedure, which led to acknowledging the inflammation pathogenesis during the phacoemulsification. Although there is still a lack of evidence, which would prove the long-term benefit of NSAIDs, they are indicated and effective when risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 118 publications
(165 reference statements)
0
2
0
Order By: Relevance
“…Pseudophakic cystoid macular edema (PCME) or Irvine–Gass syndrome is defined as intraretinal fluid in the form of cysts or central macular thickening. It remains the most common cause of decreased visual acuity after uncomplicated phacoemulsification [ 3 ]. Historically, PCME is defined with fluorescein angiography, for which the incidence was 9 to 19%.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudophakic cystoid macular edema (PCME) or Irvine–Gass syndrome is defined as intraretinal fluid in the form of cysts or central macular thickening. It remains the most common cause of decreased visual acuity after uncomplicated phacoemulsification [ 3 ]. Historically, PCME is defined with fluorescein angiography, for which the incidence was 9 to 19%.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is described in the literature that a reduction of surgical inflammation limits choroidal swelling. For example, Chen et al showed that the choroidal thickness increase was less pronounced in patients operated with a femtosecond laser, which is known to reduce the inflammatory strain on the eye [12,19]. Additionally, Cevher and Aydoğdu demonstrated that patients treated with nepafenac, an anti-inflammatory drug, had less choroidal swelling compared to controls [20].…”
mentioning
confidence: 99%
“…What has to be considered when analyzing changes in choroidal thickness after surgery is the administration of anti-inflammatory drugs. The use of NSAIDs and prednisolone eye drops suppresses the release of cytokines to a certain extent, removing the possibility of measuring the true impact of cataract surgery on the posterior segment [19]. This was demonstrated by Cevher and Aydoğdu [20], who showed that the increase in choroidal thickness was smaller in patients treated with nepafenac compared to controls, although the difference was not statistically significant.…”
mentioning
confidence: 99%